Redesign of the user interface of Us'Em mobile aplication - Conceição, Cláudia Santos da (2015)
The research presented here aims to design a feasible and adequate mobile application (app) user interface. This mobile app is part of Us'em system, designed to promote self-rehabilitation after stroke. The system is based on wearable, mobile and tracking sensors-based technology. The app works as a feedback tool, communicating Us’em system users about the frequency of their upper limb moves and about their recovery process. The mobile app aims increasing patient’s motivation in using their arm-hand through the day and improving their rehabilitation through self-training at home with continuous feedback. The design of its user interface is of great relevance, because it determines if post stoke patients can use Us’em system. The empirical part begins with interviews, questionnaires and observation of post stroke patients and physical therapists from Portugal and the Netherlands. It provides a better understanding of post stroke rehabilitation process and stroke victims’ characteristics and requirements regarding rehabilitation and mobile devices interaction. The gathered information contributed to the development of a prototype that materializes the defined Us’em app. The prototyping process ran through iterative cycles of design, implementation and evaluation to ascertain the adequacy of Us’em app user interface. The final prototype is the final product of this research project and it was evaluated through usability tests with post stroke patients from both countries aforementioned. Tests to the final prototype show it may be difficult to design a unique solution for all the users due to the wide range of their requirements. However, the core requirements of Us'em mobile app is simplicity: the number of user interface elements, the amount of information and the complexity of iteractions and functionalities of this app should be the lowest as possible. The research also allows to conclude that the user interface designed meets most of user’s requirements and it has a significant impact on the motivation of post stroke patients in moving their impaired arm-hand autonomously.